Ecological status assessment in the lower Eo estuary (Spain). The challenge of habitat heterogeneity integration: A benthic perspective - Paz, L. de (2008)
The implementation of the European Water Framework Directive (WFD) requires evaluation of the ecological status (ES) of benthic communities in coastal and transitional water systems, and the intercalibration of assessment methodologies therefore becomes a research challenge. Our aim was to test the suitability of applying the M-AMBI index to assess the status of the Eo estuary (northern coast of Spain). Our results showed that M-AMBI was influenced by the natural variability of benthic communities, and presented an apparent dependence on habitat characteristics. Consequently, the definition of homogeneous areas in transitional water systems should be based on the salinity gradient combined with other factors. To achieve an accurate ES assessment, habitat-specific reference conditions should then be defined prior to the application of M-AMBI; this necessitates dividing an estuary into several sections, which may be classified as different ESs. From this perspective, a novel approach to integrate habitat heterogeneity in a global ES assessment was tested.